Demonstration of multi‐channel 80 Gbit/s integrated transmitter and receiver for wavelength‐division multiplexing passive optical network and fronthauling applications. Issue 8 (1st April 2016) - Naughton, A.; Lai, C.P.; Talli, G.; Vaernewyck, R.; Yin, X.; Bauwelinck, J.; Qiu, X.Z.; Maxwell, G.; Smith, D.W.; Borghesani, A.; Cronin, R.; Grobe, K.; et al.
Abstract : The performance evaluation of a multi‐channel transmitter that employs an arrayed reflective electroabsorption modulator‐based photonic integrated circuit and a low‐power driver array in conjunction with a multi‐channel receiver incorporating a pin photodiode array and integrated arrayed waveguide grating is reported. Due to their small footprint, low power consumption and potential low cost, these devices are attractive solutions for future mobile fronthaul and next generation optical access networks. A BER performance of <10 −9 at 10.3 Gbit/s per channel is achieved over 25 km of standard single mode fibre. The transmitter/receiver combination can achieve an aggregate bit rate of 82.4 Gbit/s when eight channels are active.